Analysis of failure mechanisms of adhesive joints modified by a novel additive manufacturing-assisted method. (15th February 2023) - Kanani, Armin Yousefi; Wang, Xing-Er; Hou, Xiaonan; Rennie, Allan E.W.; Ye, Jianqiao
Highlights: The sacrificial water-soluble support fixtures were made with additive manufacturing technique. The mechanical performance of the joints with the modified features increased significantly. The DE model could simulate the initiation and propagation of micro-cracks inside the adhesive and along the interface. The modified bonded joints demonstrate a clear reduction in peak stress along the bond line. Abstract: The research presented in this paper used an innovative method to modify the configuration of adhesively bonded joints for improved mechanical performance. Additive manufacturing was employed to produce sacrificial support structures with a water-soluble filament (Polyvinyl Alcohol). The design freedom offered by additive manufacturing makes it easy to tailor fixtures to any geometry, which can be used to accurately make the desired fillet shape at the end of the adhesive bond line. In addition to the experimental tests, the finite element method (FEM) was used to study the stress distribution along the bond line for four different modified bonded joints, whilst the discrete element method (DEM) was used to estimate the joint failure load and crack path in the adhesive bond line due to its strength in describing the initiation and progression of micro-cracks. The results show that the novel manufacturing method can produce an accurate fillet at the end of the bond line, regardless of the adhesive type. The mechanical performance of the joints with the modified features increased significantly. Furthermore, the failure load and crack path obtained from the DEM model is in close agreement with experimental and finite element (FE) results. Hence, the failure mechanism of the hybrid joints is then summarised.